i think i have to simplify.... but the question just says:

(2y-3)^2
possible answers:
a.4y^2+9
b.4y^2-6y+9
c.4y^2-12y+9
d.4y^2+12y+9

6 answers

separate and multiply based on

FOIL
first
outer
inner
last
(2y-3)^2=

(2y-3)(2y-3) then use foil and multiply the first term, outer term, inner terms then last terms .

(2y-3)(2y-3)

first terms multiplied

2y*2y= 4y^2

outer terms multiplied

2y*(-3)=-6y

inner terms multiplied

(-2y)*3=-6y

last terms multiplied

(-3)*(-3)=9

Now combined FOIL (first outer inner and last terms )

4y^2-6y-6y+9= but now you can combine the -6y's so (-6y-6y=-12y)

and you get 4y^2-12y+9
duplicate post
inner terms multiplied

2y*(-3)=-6y

it is the same as the outer terms multiplied (the negative was misplaced before)
Oh..it was a duplicate?
Oh well I solved it Dr.Bob.=D
anyways..ha
thank you...
Your welcome =)